Defective Neutrophil Transendothelial Migration and Lateral Motility in ARPC1B Deficiency Under Flow Conditions - Kempers, Lanette; Sprenkeler, Evelien G. G.; van Steen, Abraham C. I.; van Buul, Jaap D.; Kuijpers, Taco W. (Frontiers in Immunology, 2021)
The actin-related protein (ARP) 2/3 complex, essential for organizing and nucleating branched actin filaments, is required for several cellular immune processes, including cell migration and granule exocytosis. Recently, genetic defects in ARPC1B, a subunit of this complex, were reported. Mutations in ARPC1B result in defective ARP2/3-dependent actin filament branching, leading to a combined immunodeficiency with severe inflammation. In vitro, neutrophils of these patients showed defects in actin polymerization and chemotaxis, whereas adhesion was not altered under static conditions. Here we show that under physiological flow conditions human ARPC1B-deficient neutrophils were able to transmigrate through TNF-α-pre-activated endothelial cells with a decreased efficiency and, once transmigrated, showed definite impairment in subendothelial crawling. Furthermore, severe locomotion and migration defects were observed in a 3D collagen matrix and a perfusable vessel-on-a-chip model. These data illustrate that neutrophils employ ARP2/3-independent steps of adhesion strengthening for transmigration but rely on ARP2/3-dependent modes of migration in a more complex multidimensional environment.